Hubungan Pengetahuan dan Sikap dengan Pemeriksaan HIV pada Ibu Hamil di Puskesmas Argamakmur Kabupaten Bengkulu Utar - Tria Nopi Herdiani; Mika Oktarina; Eva Herawati (Akademi Kebidanan Aifa Husada Madura, 2020)
Prevention of HIV Transmission from Mother to Child (PPIA) is a program of transmission of HIV virus transmission of HIV which is carried out through HIV prevention and control activities on an ongoing basis. The purpose of this study was to study the relationship of knowledge and attitudes with HIV testing in pregnant women in the Argamakmur Community Health Center in North Bengkulu Regency. The design used in analytic survey research with Cross Sectional research. The population in the study were all pregnant women who visited the Argamakmur Health Center in January to April 2019, leaving 162 people. Samples were taken by accidental sampling as many as 38 respondents. The data used are primary data and secondary data. Data were analyzed using univariate and bivariate analysis with the Chi-Square test (c2) and Contingency Coefficient (C). The results were obtained from 38 samples of 23 (60.5%) mothers who never had an HIV test, 16 (42.1%) mothers with insufficient knowledge, as many as 22 (57.9%) mothers with an unsupportive attitude and, there were relationship between knowledge and HIV testing in pregnant women with a moderate relationship category, there is a relationship between attitude to HIV testing in pregnant women with a moderate relationship category. It is hoped that Puskesmas can work together to improve HIV testing by pregnant women through providing assistance to pregnant women about HIV testing for pregnant women.